2021
DOI: 10.3389/fendo.2021.652444
|View full text |Cite
|
Sign up to set email alerts
|

Sex Differences in Brown Adipose Tissue Function: Sex Hormones, Glucocorticoids, and Their Crosstalk

Abstract: Excessive fat accumulation in the body causes overweight and obesity. To date, research has confirmed that there are two types of adipose tissue with opposing functions: lipid-storing white adipose tissue (WAT) and lipid-burning brown adipose tissue (BAT). After the rediscovery of the presence of metabolically active BAT in adults, BAT has received increasing attention especially since activation of BAT is considered a promising way to combat obesity and associated comorbidities. It has become clear that energ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 180 publications
2
39
0
Order By: Relevance
“…DIO2 catalyzes the conversion of T4 to its active form, T3, which stimulates fatty acid oxidation and mitochondrial respiration in BAT [41]. Sex differences in energy expenditure can be explained by the inducing effect of estrogens on BAT activity and thermogenesis [42]. The increased expression of Ppara, Fgf21, and Pgc1 in the liver, along with an increased level of adiponectin in the blood, indicates the more intensive oxidation of fats in the liver in females than in males, since PPARa [43], PGC1 [44], FGF21, and adiponectin activate fatty acid oxidation in the liver [45].…”
Section: Discussionmentioning
confidence: 99%
“…DIO2 catalyzes the conversion of T4 to its active form, T3, which stimulates fatty acid oxidation and mitochondrial respiration in BAT [41]. Sex differences in energy expenditure can be explained by the inducing effect of estrogens on BAT activity and thermogenesis [42]. The increased expression of Ppara, Fgf21, and Pgc1 in the liver, along with an increased level of adiponectin in the blood, indicates the more intensive oxidation of fats in the liver in females than in males, since PPARa [43], PGC1 [44], FGF21, and adiponectin activate fatty acid oxidation in the liver [45].…”
Section: Discussionmentioning
confidence: 99%
“…Fetal sex was not determined in the current study. Given the presence of sexual dimorphism in BAT mass and function in adult rodents and humans [ 39 ], fetal sex will need to be considered in future studies into fetal BAT development.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to Ldb1 ΔBAT male mice, which had significant reductions in EE at all temperatures, female Ldb1 ΔBAT mice only displayed reduced EE at 22 °C. Additionally, a cold challenge revealed that male Ldb1 ΔBAT mice displayed the greatest reduction in core body temperature at 4 h. Sex differences in thermogenesis may be attributed to variations in basal uncoupling capacity, sympathetic activity, fat mass composition, and hormone signaling [ 41 , 44 ]. This difference also extends to metabolic parameters, like glucose and lipid homeostasis [ 45 ].…”
Section: Discussionmentioning
confidence: 99%